An invasive plant Sonchus asper (L.) Hill: A review of its ethnopharmacology, phytochemistry, and pharmacological properties (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
India is well known for medicinal plants because of rich plant biodiversity. Kumaun Himalayan region of Uttarakhand state occupies a great place in having good number of medicinal plants. The uses of plants in the indigenous cultures of developing countries are numerous and diverse. In a developing country, 65% population is dependent upon traditional medicinal system. The plant based traditional medicinal system play an important role in curing the health from various diseases all over the world. The present review reveals the updated information regarding the ethnopharmacology, phytochemistry, and pharmacological properties of an invasive plant Sonchus asper (L.) Hill. For this study, an extensive and intensive field survey by visiting the nearby villages of Nainital district was carried out along with detailed literature survey. Multitudinous ethnic properties and pharmacological study may help in development of new drug for the treatment of cancer and infectious diseases from this plant. The documentation of isolated compounds may afford new drug entity for pharmacy sector with lesser cost and more efficacy.